Republic of Lithuania : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that growth in Lithuania has remained resilient, despite challenges in the external environment. Strong domestic demand growth on the back of improving labor market conditions underpinned real GDP growth of 2.9 percent in 2014. Exports held up reasonably well despite Russian import bans. Growth should remain largely unchanged at 2.8 percent from last year in 2015, as positive external factors counterbalance negative ones and domestic demand remains robust. The main policy challenge will be to secure reasonably rapid convergence with living standards in western Europe going forward.